Health Capacity Development Through Telemedicine in Africa - Mars, M. (Yearbook of Medical Informatics, 2010)
Objective: The aim of this paper is to identify and report the issues facing human capacity development through the use of telemedicine in Sub-Saharan Africa.Methods: Data were obtained through literature review and personal observation.Results: Sub-Saharan Africa has a great burden of disease and an extreme shortage of health workers. Its countries are poor and the majority of its population rural. Telemedicine for clinical practice and education of health workers is seen as a possible means of addressing some of the health problems of Africa. A number of factors have been identified that impede the use of telemedicine in sub-Saharan Africa. These include, poverty, shortage of human resources, very limited existing infrastructure, lack of connectivity, high connectivity costs, lack of capacity development and policy issues. Examples of successful use of telemedicine and tele-educational programmes in Africa to develop capacity in health are given.Conclusions: Initiatives to develop capacity through tele-education appear to have been well received and are more successful than clinical telemedicine. There is need to raise awareness of telemedicine if it is to assist in developing ehealth capacity in Africa.
Keywords: Africa; telemedicine; education; capacity development